2017
DOI: 10.1101/108225
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Caenorhabditis elegansBMP Transcriptional Program Implicates Collagen Genes in Body Size Regulation

Abstract: 18Body size is a tightly regulated phenotype in metazoans that is dependent on both 19 intrinsic and extrinsic factors. While signaling pathways such as insulin, Hippo, and myostatin 20 are known to control organ and body size, the downstream effectors that mediate their effects are 21 still poorly understood. In the nematode C. elegans, a Bone Morphogenetic Protein (BMP)-22 related signaling pathway is the major regulator of growth and body size. DBL-1, the BMP-23 related ligand, is secreted by neurons and bo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Nematode cuticles mostly consist of collagen (more than 80%) [101]. It has been shown that epidermal collagen genes can act as positive regulators, dose-dependent regulators, and negative regulators of body size [102]. In connection with the damage to the cuticle, which was observed, disruption of epidermal gene expression may caused inhibition of C. elegans growth.…”
Section: Effect On the Worm Survivalmentioning
confidence: 99%
“…Nematode cuticles mostly consist of collagen (more than 80%) [101]. It has been shown that epidermal collagen genes can act as positive regulators, dose-dependent regulators, and negative regulators of body size [102]. In connection with the damage to the cuticle, which was observed, disruption of epidermal gene expression may caused inhibition of C. elegans growth.…”
Section: Effect On the Worm Survivalmentioning
confidence: 99%